Microbial exposure drives polyclonal expansion of innate γδ T cells immediately after birth - Ravens, Sarina; Fichtner, Alina S.; Willers, Maike; Torkornoo, Dennis; Pirr, Sabine; Schoening, Jennifer; Deseke, Malte; Sandrock, Inga; Bubke, Anja; Wilharm, Anneke; Dodoo, Daniel; Egyir, Beverly; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Starting at birth, the immune system of newborns and children encounters and is influenced by environmental challenges. It is still not completely understood how γδ T cells emerge and adapt during early life. Studying the composition of T cell receptors (TCRs) using next-generation sequencing (NGS) in neonates, infants, and children can provide valuable insights into the adaptation of T cell subsets. To investigate how neonatal γδ T cell repertoires are shaped by microbial exposure after birth, we monitored the γ-chain (TRG) and δ-chain (TRD) repertoires of peripheral blood T cells in newborns, infants, and young children from Europe and sub-Saharan Africa. We identified a set of TRG and TRD sequences that were shared by all children from Europe and Africa. Thesewere primarily public clones, characterized by simple rearrangements of Vγ9 and Vδ2 chains with low junctional diversity and usage of non-TRDJ1 gene segments, reminiscent of early ontogenetic subsets of γδ T cells. Further profiling revealed that these innate, public Vγ9Vδ2+ T cells underwent an immediate TCR-driven polyclonal proliferation within the first 4 wk of life. In contrast, γδ T cells using Vδ1+ and Vδ3+ TRD rearrangements did not significantly expand after birth. However, different environmental cues may lead to the observed increase of Vδ1+ and Vδ3+ TRD sequences in the majority of African children. In summary, we show how dynamic γδ TCR repertoires develop directly after birth and present important differences among γδ T cell subsets.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Neonatal II t cells; Non-vI9vI2; Postnatal tcr repertoire focusing; Trg and trd repertoires; VI9vI2